2021
DOI: 10.4103/ijo.ijo_1293_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and surgical outcomes of complications of proliferative diabetic retinopathy in young adults with type 1 diabetes mellitus versus type 2 diabetes mellitus - A comparative observational study

Abstract: Purpose: To evaluate the clinical profile, visual outcomes, and complications among young adult patients with type 1 diabetes mellitus (insulin-dependent DM-T1DM) in comparison with patients with type 2 diabetes mellitus (T2DM) undergoing vitrectomy for complications of proliferative diabetic retinopathy (PDR). Methods: A retrospective review of patients between 18 and 45 years with T1DM undergoing vitrectomy for complications of PDR between June 2017 and June 2019, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
(59 reference statements)
0
10
2
1
Order By: Relevance
“…The course of diabetes mellitus may rapidly change with progression of diabetic complications if other general disorders, namely systolic hypertension, hyperlipidaemia, obesity or microalbuminuria, occur. It was reported that the prevalence of chronic kidney disease is higher in type 1 DM patients and young diabetics [ 17 , 19 ]. In patients requiring vitrectomy, renal compromise may be a reason for higher risk of intraoperative and postoperative bleeding, delayed wound healing and an increase in mortality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The course of diabetes mellitus may rapidly change with progression of diabetic complications if other general disorders, namely systolic hypertension, hyperlipidaemia, obesity or microalbuminuria, occur. It was reported that the prevalence of chronic kidney disease is higher in type 1 DM patients and young diabetics [ 17 , 19 ]. In patients requiring vitrectomy, renal compromise may be a reason for higher risk of intraoperative and postoperative bleeding, delayed wound healing and an increase in mortality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to advancements in vitrectomy in recent years, the rates of primary reattachment and final attachment of retina after vitrectomy for TRD have increased, ranging from 86.3 to 100% [ 18 , 19 , 32 , 40 , 43 ]. Primary reattachment of retina in our patients was achieved in 88.9% and 95.5% of the eyes from the DM1 and DM2 groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5–8 However, the compliance of purely Western medical treatment is poor and easily affects the quality of life of T1DM patients, which makes it difficult for many patients to achieve strict control of blood glucose in daily life, resulting in significant blood glucose fluctuations and multiple complications. 9 , 10 Furthermore, T1DM has been confirmed that it is related to various molecular mechanisms, including autophagy, oxidative stress, inflammation and apoptosis of pancreatic β-cells. 11–13 Yet, though significant advances have been made since the past several decades, the potential therapeutic strategies and the exact molecular mechanisms of T1DM remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although panretinal photocoagulation (PRP) has been the treatment of choice for delaying the diabetic retinopathy process and preventing visual loss, there remains a high number of patients progressing to the advanced stages, such as vitreous hemorrhage and tractional retinal detachment, and subsequently requiring pars plana vitrectomy (PPV) to clear vitreous haemorrhage (VH) and reattach the retina. However, PPV for patients with PDR can often be challenging ( 2 ). Vitreous removal, membrane peeling and membrane delamination can be difficult procedures due to the tight adhesions formed between the fibrovascular membrane and the retina, which can lead to intraoperative haemorrhages and iatrogenic breaks ( 3 ).…”
Section: Introductionmentioning
confidence: 99%